Table of Content - -, (Journal of Humanities & Social Sciences, 2024)
Table of Content:1. Ecotourism for the Sustainability of Protected Areas Soqotra Island: Case Study – YemenDr. Bardees Taher Alokab2. Territorial Information System and the Enhancement of Territorial Governance Mechanisms  in the Countryside of Taourirt Province (Eastern Region – Morocco)Dr. JAOUAD EL BAZOUI, Dr. Mohammed LAKHDARI, Dr. Mohamed AZIACH3. Solidarity And Social Economy and the Question of Territorial Governance: The Case of the Almond Chain Development Program in the Province of Taourirt- East Region (Morocco)Dr. Mohammed LAKHDARI, Dr. Mohamed AZIACH, Dr. Jaouad El-BAZOUI4. Women driving a car and its role in achieving self-independence and raising the level of quality  of life among a sample of working women in the city of JeddahMs. Najwa Abdullah Al-Gamdi, Dr. Suha Omar Alharthi5. Arab-Zionist Struggle Terminology of Place NamingDr. Amal Mahmoud Abu Own, Prof. Ihsan Yacoub Al-Deek6. The natural components of mountain Shada and their role in achieving sustainable tourismMs. Zahra Ahmed Alzahrani
Keywords: Journal of Human and Social Sciences